Geobacter abundance in soil regulate by pH and iron-bearing minerals - Bai, Yinping; Dai, Qianli; Guo, Junkang; Fu, Wei; Yun, Juanli; Wang, Fusong; Huang, Jing; Zhang, Rongping; Yang, Gang (Frontiers in Ecology and Evolution, 2025)
As an electrogenic bacterium, Geobacter plays a crucial role in the geochemical cycles of arable soil. However, little is known about the existence of Geobacter and its impact factors in paddy soil and purple soil. We determined Geobacter in paddy soil and purple soil in Sichuan Basin, China. The data reveal that soil pH in arable soils is the main factor in determining Geobacter abundance, and the coefficient of determination is as high as 72.5%. Iron-bearing minerals (IBM) have a positive relationship with Geobacter abundance when their content exceeds 9%. Overall, Geobacter abundance in paddy soil is higher than that in purple soil. Geobacter in paddy soil prefers acidic environment, whereas Geobacter in purple soil prefers neutral environment. Geobactor in paddy soil prefers acidic environment, which may be related to long-term irrigation and drainage in paddy fields. In addition, we found that the soil pH in the Sichuan Basin decreased by 0.7 over a period of forty years, providing evidence for the succession of Geobacter species in this region that prefer neutral and acidic environments. The acidified soil environment in the Sichuan Basin is conducive to the survival of Geobacter. This condition directly influences the iron heterotrophic iron reduction process carried out by Geobacter and subsequently impacts soil carbon emissions.